John Gilbert Clark papers - Clark, John Gilbert, 1770-1824.
Correspondence and miscellaneous papers. Includes the logbook (1798-1799) of the schooner Frederick.
Shipowner.
Collection material in English.
Keywords: Ship's papers -- 18th century; Frederick (Schooner); Shipowners